Apple pomace improves the quality of pig manure aerobic compost by reducing emissions of NH3 and N2O - Hui Mao (Nature Portfolio, 2017)
Abstract In this study, the effects of apple pomace (AP) addition (0%, 5%, 10%, and 20% on a dry weight basis, named as control, AP1, AP2, and AP3) and citric acid (CA) addition on nitrogen conservation were investigated during aerobic composting of pig manure. Gaseous emissions of NH3 and N2O were inhibited by AP and CA addition, with AP’s effect greater. The inhibition improved with increasing AP addition. The AP3 treatment was the most effective on NH3 adsorption and transformation to $${{\bf{NH}}}_{{\bf{4}}}^{{\boldsymbol{+}}}$$ NH 4 + -N, improved with subsequent transformation to $${{\bf{NO}}}_{{\bf{3}}}^{{\boldsymbol{-}}}$$ NO 3 − -N, and inhibition of N2O and $${{\bf{NO}}}_{{\bf{2}}}^{{\boldsymbol{-}}}$$ NO 2 − production. Compared with control, AP3 showed the highest inhibition of accumulated NH3 and N2O emission, by 57% and 24%, respectively, and with a 19% increase of total Kjeldahl nitrogen in the compost. The further pot experiment proved the application of the AP amendment compost could improve the yield and trace element nutrient accumulation in Chinese cabbage when planted in a typical Zn-deficient soil. This study illustrates that AP application benefits both compost nitrogen conservation and fertilizer quality.